THE IMPACT OF TOURISM ON RURAL DEVELOPMENT - EXAMPLE OF UNDEVELOPED VILLAGES IN REPUBLIC OF SERBIA - Drago Cvijanović; Tamara Gajić; Dušica Cvijanović (Economic Review)
The aim of the research in this paper is to determine which factors the local population identifies as those that can, through the development of tourism, most influence or predict rural development or revitalization in the Republic of Serbia. In order to examine this, the survey was conducted during 2019, on a total sample of 680 respondents, in 45 rural municipalities in the country. The authors used a modified questionnaire, containing four groups of factors, with adequate 22 questions for research on a given issue. The SPSS AMOS software, version 26.00, was used for data analysis and processing. The authors checked the reliability of the questionnaire, whose value proved to be very good, and confirmed the grouping into exactly four groups of factors by Factor analysis. Descriptive statistical analysis yielded average scores for given items. The obtained suitability indices indicated the agreement of the Structural structural equation modeling (SEM) with the data, as well as the quality of the research and the confirmation of the hypotheses. The obtained results of the SEM analysis showed that there is no statistically significant difference in the impact of given factors in predicting rural development, and that the local population has a positive attitude about the impact of tourism on rural development.